Histone 3 and 4 acetylation patterns in nodular goiters and well-differentiated thyroid tumors compared with normal thyroid tissue - Chhetri, Nishal; Keelawat, Somboon (Chulalongkorn Medical Journal, 2024)
Background: Histone acetylation is a well-recognized epigenetic process involved in various cancer development pathways. However, thus far, its role in thyroid tumors and nodular goiter has been barely investigated. Objectives: This study aimed to assess histone modifications (hypoacetylation or hyperacetylation) in various thyroid lesions, including papillary thyroid carcinoma (PTC), follicular thyroid carcinoma (FTC), follicular adenoma (FA), and nodular goiter, through immunohistochemistry with anti-acetyl histone 3 (H3K9/ K14ac) and 4 (H4K5, 8, 12, and 16ac) antibodies, compared with their normal counterparts to elucidate their role in the development of these lesions. Methods: Formalin-fixed paraffin-embedded sections of surgically resected PTC, FA, FTC, and nodular goiter samples were collected from the archives of the Department of Pathology, Faculty of Medicine, Chulalongkorn University, from 2016 to 2018. These sections were then stained with anti-acetyl histone 3 (H3K9/K14ac) and 4 (H4K5, 8, 12, and 16ac) antibodies. Aperio ImageScope was used to automatically score the intensity and proportion of immunostaining of the lesions and their normal thyroid tissue counterparts. Results: A total of 97 malignant thyroid lesions, including (28 FA, 50 PTC, and 19 FTC samples), and 50 nodular goiters were evaluated. The deacetylation of both anti-acetyl histone 3 (H3K9/K14ac) and 4 (H4K5, 8, 12, and 16ac) antibodies was detected in nodular goiter (P = 0.0016 and P < 0.0001, respectively) in comparison with their normal counterparts. However, the difference in the acetylation status of FTC, PTC, and FA were not significant compared with that of their normal counterparts (P > 0.05 in all cases). Conclusion: For the first time, this study demonstrates the H3 and H4 deacetylation of nodular goiters compared with their normal tissue counterparts. In contrast, these epigenetic events are not found in welldifferentiated thyroid neoplasms (FA, FTC, and PTC).